Slow Hole Transfer Kinetics Lead to High Blend Photoluminescence of Unfused A–D–A′–D–A‐Type Acceptors with Unfavorable Highest Occupied Molecular Orbitals Offset. Issue 7 (29th April 2022) - Zou, Xinhui; Yu, Han; Qi, Zhenyu; Liu, Bin; Xing, Zengshan; Chan, Christopher C. S.; Chow, Philip C. Y.; Pan, Ding; Yan, He; Wong, Kam Sing
Abstract : Nonfullerene organic photovoltaics (OPVs) with small energetic offset between donor and acceptor can provide a much‐reduced voltage loss and power conversion efficiencies over 18%, challenging the previous understanding of the charge generation mechanisms. Herein, a study is presented on nonfullerene OPVs with negative energetic offsets, by investigating a model system which exhibits poor photoluminescence quenching (PLQ, ≈17%) yet reasonably high external quantum efficiency (EQE, ≈50%). It is found that the discrepancy between the poor PLQ and relatively high EQE is dependent on the measurement conditions, namely, short or open circuit, under which the devices exhibit differences in charge generation. Transient absorption spectroscopy shows surprisingly slow hole transfer on nanosecond timescale. It is revealed that the poor PLQ/high radiative recombination originates from an increased back transfer from free carriers to the singlet excitons under open circuit. It is made possible by the slow charge‐transfer (CT) kinetics, long‐lived CT states, and emissive excitons. Despite the negative offset, the charge generation can be relatively efficient under short circuit. The results suggest that the PLQ under open circuit is not necessarily a good indicator of charge separation efficiency and provide new insight to efficient charge generation of OPVs with unfavorable energy offsets. Abstract : The model system PTQ10:BOC‐4F with high blend photoluminescence and negative offset is found to have a well‐established equilibrium between singlet excitons, charge transfer states, and free charges. The discrepancy between high charge generation efficiency and low photoluminescence quenching is due to the shift of the equilibrium and slow hole transfer under short circuit and open circuit.